KEMAMPUAN KOMITMEN ORGANISASI MEMODERASI PENGARUH PERENCANAAN ANGGARAN DAN KOMPETENSI SDM PADA PENYERAPAN ANGGARAN PEMERINTAH KABUPATEN TABANAN - Lestari Dewi, Ni Luh Putu; Dwirandra, A.A.N.B; Wirakusuma, Made Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
ABSTRACT The inconsistency of results of research on the effect of budget planning and competence of human resources (HR) at the absorption indicates other factors that influence to encourage researchers to include a commitment to the organization as the moderating variable. The sampling method used in this research is the method of probability sampling  with technique  proportionate stratified random sampling. Total respondents 251 managers of the budget, including the Budget User, Financial Administration Officer, the Technical Activities Executive Officer, and Treasurer Expenditure. The analysis technique used is regression analysis moderation (Moderated Regression Analysis).The results showed that the positive effect of budget planning, and competency negative effect on the absorption of the budget and the commitment the organization is not able to strengthen budget planning and is able to strengthen the capacities of human resources in Tabanan District Government budget absorption.
Keywords: Keywords: planning, competence HR, organizational commitment and budget absorption.